Synthesis, structure, physicochemical properties and antibacterial activity of 1,2,4-triazoles-3-thiols and furan derivatives - Zazharskiy, Vladymyr; Zazharskiy, Volodymyr; Zazharskyi, Vladymyr; Zazharskyi, Volodymyr; Zazharskiy, V.; Zazharskyi, V.; Zazharskiy, Volodymyr V.; Zazharskiy, V. V.; Zazharskyi, V. V.; Zazharsky, V. V.; Зажарський, Володимир Володимирович; Parchenko, M.; et al. (Ukrainian State University of Chemical Technology, 2019)
New compounds, 5-R2-2- (furan-2-yl-,5-bromofuran-2-yl) thiazolo [3,2-b][1,2,4] triazole-4 (5H)-ones, have been synthesized with a high yield for the first time. Molecules of these compounds contain the residuals of 1,2,4-triazole-3-thiols and furan. The reaction of their reduction by an excess of sodium borohydride was investigated. The structure of the synthesized compounds was confirmed by NMR 1H spectroscopy, X-ray microanalysis and chromatography. The reduction of 5-R2-2-(furan-2-yl-,5-bromofuran-2-yl) thiazolo [3,2-b] [1,2,4] triazole-4 (5H)-ones in a methanol medium in the presence of a triple quantity of sodium borohydride occurs with the formation of corresponding 3-R2-2-((3-(furan-2-yl, 5-bromofuran-2-yl)-1,2,4-triazol-5-yl) thio)-prop-2-en-1-oles. The antibacterial activity of the synthesized compounds towards the cryogenic strains of Enterococus faecalis, Proteus mirabilis, Proteus vulgaris, Serratia marcense, Salmonella adobraco, Salmonella typhimurium, Staphylococcus epidermidis, Bacillus subtilis, Listeria ivanovi, Listeria іnnocua, Listeria monocytogenes, Campylobacter jejuni, Rhodococcus equi and Candida albicans was investigated. According to the obtained data, the investigated compounds can compete with kanamycin, a natural broad-spectrum antibiotic from the second generation of aminoglycosides, the action spectrum of which includes gram-positive and gram-negative microorganisms. The compounds involved may be recommended for further investigations concerning multi-resistant strains of microorganisms. Нові сполуки, 5-R2-2- (фуран-2-іл-, 5-бромофуран-2-іл) тіазоло [3,2-b] [1,2,4] триазол-4 (5Н) -он, вперше синтезовано з високим виходом. Молекули цих сполук містять залишки 1,2,4-триазол-3-тіолів та фуран. Досліджено реакцію їх відновлення надлишком борогідриду натрію. Структуру синтезованих сполук було підтверджено ЯМР-спектроскопією 1Н, рентгенівським мікроаналізом та хроматографією. Відновлення 5-R2-2- (фуран-2-іл-, 5-бромофуран-2-іл) тіазоло [3,2-b] [1,2,4] триазол-4 (5Н) -онів у метанольне середовище в присутності потрійної кількості боргідриду натрію відбувається з утворенням відповідного 3-R2-2 - ((3- (фуран-2-іл, 5-бромфуран-2-іл) -1,2,4- триазол-5-іл) тио) -проп-2-ен-1-ол. Досліджували антибактеріальну активність синтезованих сполук по відношенню до криогенних штамів Enterococus faecalis, Proteus mirabilis, Proteus vulgaris, Serratia marcense, Salmonella adobraco, Salmonella typhimurium, Staphylococcus epidermidis, Bacillus subtilis, Listeria ivanovi, Listeria іnnocua, Listeria monocytogenes, Campylobacter jejuni, Rhodococcus equi та Candida albicans. Відповідно до отриманих даних, досліджувані сполуки можуть конкурувати з канаміцином, природним антибіотиком широкого спектру дії аміноглікозидів другого покоління, спектр дії якого включає грампозитивні та грамнегативні мікроорганізми. Залучені сполуки можуть бути рекомендовані для подальших досліджень щодо багатостійких штамів мікроорганізмів.
Синтез, структура, фізико-хімічні властивості та антибактеріальна активність 1,2,4-триазол-3-тіолів та похідних фурану
Зажарський Володимир Володимирович https://orcid.org/0000-0003-2674-2494 Давиденко Павло Олександрович https://orcid.org/0000-0002-8425-3835 Кулішенко Олег Миколайович https://orcid.org/0000-0001-6801-2380 Зажарська Надія Миколаївна https://orcid.org/0000-0002-8328-6440 Боровик Ірина Володимирівна https://orcid.org/0000-0001-5958-8396
Keywords: antibacterial activity; антибактеріальна активність; cyclization; циклізація; 1,2,4-triazole; 1,2,4-триазол; reduction; відновлення; physicochemical properties; фізико-хімічні властивості